The Effect of Exchange Rate, Inflation, FDI, and Domestic Consumption on GDP Through Non-Oil and Gas Exports, Indonesia - Hasbiullah, Hasbiullah; Nurilmih, Nurilmih (Technium Social Sciences Journal, 2022)
This research aims to analyze the effect of the exchange rate (ER), inflation (Inf), FDI, and domestic consumption (DC) on GDP in Indonesia directly or indirectly through non-oil and gas export (Ngx) as a intervening variable using annual time-series data from 2000 until 2020 using path analysis techniques processed by the E-views application. The results of direct influence in this research show that the exchange rate, inflation, and domestic consumption have a significant effect while FDI do not has a significant effect on non-oil and gas exports. Then, the influence on GDP show that the exchange rate, domestic consumption, non-oil and gas export (Ngx) have a significant effect while Inflation (Inf), and FDI do not has a significant effect. The next result of indirect influence in this research show that, the inflation (Inf) and FDI have a significant effect while exchange rate and domestic consumption (DC) do not has a significant effect on GDP.